2021
DOI: 10.3390/ma14010208
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan and Kynurenine Enhances the Stemness and Osteogenic Differentiation of Bone Marrow-Derived Mesenchymal Stromal Cells In Vitro and In Vivo

Abstract: Aging tissues present a progressive decline in homeostasis and regenerative capacities, which has been associated with degenerative changes in tissue-specific stem cells and stem cell niches. We hypothesized that amino acids could regulate the stem cell phenotype and differentiation ability of human bone marrow-derived mesenchymal stromal cells (hBMSCs). Thus, we performed a screening of 22 standard amino acids and found that D-tryptophan (10 μM) increased the number of cells positive for the early stem cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Quinolinate phosphoribosyl transferase protein (QPRT) catabolizes quinolinic acid to nicotinic acid mononucleotide for de novo NAD synthesis (kynurenine pathway). It has been shown that both L-kynurenine and L-tryptophan significantly increase the stemness and migration of hBMSC, in addition to suppressing adipogenesis [88][89][90]. The rapid degradation of QPRT may thus be necessary for the loss of self-renewal capacity in hASC and triggering adipogenesis.…”
Section: Posttranscriptional Regulation Of Differential Abundantmentioning
confidence: 99%
“…Quinolinate phosphoribosyl transferase protein (QPRT) catabolizes quinolinic acid to nicotinic acid mononucleotide for de novo NAD synthesis (kynurenine pathway). It has been shown that both L-kynurenine and L-tryptophan significantly increase the stemness and migration of hBMSC, in addition to suppressing adipogenesis [88][89][90]. The rapid degradation of QPRT may thus be necessary for the loss of self-renewal capacity in hASC and triggering adipogenesis.…”
Section: Posttranscriptional Regulation Of Differential Abundantmentioning
confidence: 99%
“… 28 Multiple studies have implied that Kyn contributes to the immune-tolerant TME by several mechanisms, including suppressing tumor-reactive effector T-cell responses 29 and inhibiting the expansion of effector T cells. 30 , 31 Thus, we used a CSFE assay to determine the effect of Kyn on T cell proliferation. Kyn of 120 μM significantly inhibited the proliferation of CD8 + T cells ( Figure 1(e) ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using different cell lines corroborate the lack of effect of tryptophan on cell proliferative capacity [ 40 41 ]. Concerning differentiation, a recent study published by Pham et al [ 42 ] has shown that tryptophan induces the differentiation of bone marrow-derived mesenchymal stromal cells. However, the ability of these cells to maintain a permanent undifferentiated phenotype challenges the comparison with the findings obtained in the present work.…”
Section: Discussionmentioning
confidence: 99%